Genetically inducible and reversible zebrafish model of systemic inflammation - Kevin A. Lanham (Biology Open, 2022)
The inflammatory response is a vital defense mechanism against trauma and pathogen induced damage, but equally important is its appropriate resolution. In some instances of severe trauma or sustained infection, inappropriate and persistent activation of the immune response can occur, resulting in a dangerous systemic inflammatory response. Untreated, this systemic inflammatory response can lead to tissue damage, organ shutdown, and death. Replicating this condition in tractable model organisms can provide insight into the mechanisms involved in the induction, maintenance, and resolution of inflammation. To that end, we developed a non-invasive, inducible, and reversible model of systemic inflammation in zebrafish. Using the Gal4-EcR/UAS system activated by the ecdysone analog tebufenozide, we generated transgenic zebrafish that allow for chemically induced, ubiquitous secretion of the mature form of zebrafish interleukin-1β (Il-1βmat) in both larval and adult developmental stages. To ensure a robust immune response, we attached a strong signal peptide from the Gaussia princeps luciferase enzyme to promote active secretion of the cytokine. We observe a dose-dependent inflammatory response involving neutrophil expansion accompanied by tissue damage and reduced survival. Washout of tebufenozide permits inflammation resolution. We also establish the utility of this model for the identification of small molecule anti-inflammatory compounds by treatment with the immunosuppressant rapamycin. Taken together, these features make this model a valuable new tool that can aid in identifying potential new therapies while broadening our understanding of systemic inflammation, its impact on the immune system, and its resolution.